The Effectiveness of Psychological Capital Training to Improve the Optimism Attitude in Mandiri Enterprises: Literature Review - Tsafitri Rinti Taddaga; Abdul Muhid (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
A pandemic due to the coronavirus (covid-19) outbreak has caused many negative impacts, one of which is in the form of massive losses in the economic sector. Business actors are under pressure from a significant decline in income; as a result, many of them experience a decrease in optimism about the sustainability of their business. However, there are several ways to increase optimism, one of which is psychological capital training. This study aims to look at psycap training in increasing the optimism of business actors in dealing with the coronavirus pandemic. This study uses a literature review method with the data source in the form of research data that has been done previously. The results of the literature review show that psychological capital training can increase one's optimism so that it can use to increase the optimism of business actors.